2016
DOI: 10.1007/s00213-016-4263-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute alcohol intoxication on the cognitive mechanisms underlying false facial recognition

Abstract: RationaleFalse face recognition rates are sometimes higher when faces are learned while under the influence of alcohol. Alcohol myopia theory (AMT) proposes that acute alcohol intoxication during face learning causes people to attend to only the most salient features of a face, impairing the encoding of less salient facial features. Yet, there is currently no direct evidence to support this claim.ObjectivesOur objective was to test whether acute alcohol intoxication impairs face learning by causing subjects to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 40 publications
5
22
0
Order By: Relevance
“…We will refer to this as the disinhibition account . This idea is in line with increased choosing rates in intoxicated versus sober participants reported in a face recognition study (Colloff & Flowe, ).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…We will refer to this as the disinhibition account . This idea is in line with increased choosing rates in intoxicated versus sober participants reported in a face recognition study (Colloff & Flowe, ).…”
Section: Introductionsupporting
confidence: 74%
“…For example, Read et al () compared identification performance for an intruder (salient) versus a bystander (peripheral). Colloff and Flowe () manipulated facial distinctiveness, the idea being that distinctive (i.e., salient) faces should be less affected by intoxication compared with nondistinctive ones. Contrary to outcomes predicted by alcohol myopia theory, performance differed neither as a function of target salience (Read, Yuille, & Tollestrup, ) nor as a function of facial distinctiveness (Colloff & Flowe, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reasoned that intoxicated participants in their study focused on a salient feature (i.e., hairstyle) of the ‘culprit’, which led them to misidentify the innocent suspect in the perpetrator absent showup who had a similar feature. However, a recent study found that participants who were intoxicated during encoding were no more likely than sober participants to be influenced by distinctive features during a basic face recognition task, regardless of whether they were intoxicated versus sober at test (Colloff & Flowe, 2016). In this study, participants who had studied faces while intoxicated were more likely to false alarm to any face, with or without a distinctive feature, suggesting that intoxicated participants were basing their recognition decisions on familiarity rather than identity‐based information.…”
Section: Background: the Effects Of Alcohol On Identification Accuracymentioning
confidence: 99%
“…For example, moderately intoxicated participants in an old-new face recognition experiment were found to make more false identifications of same-race faces than sober controls, a reduction of the own-race face processing bias the study's authors attribute to alcohol disrupting the expert encoding of same-race faces (Hilliar, Kemp & Denson, 2010). Among studies incorporating more forensically relevant face memory tasks (Altman, Schreiber Compo, McQuiston, Hagsand, & Cervera, 2018;Bayless, Harvey, Kneller, & Frowd, 2018;Colloff & Flowe, 2016;Dysart, Lindsay, MacDonald, & Wicke, 2002;Flowe et al, 2017;Hagsand, Roos af Hjelmsäter, Granhag, Fahlke, & Söderpalm-Gordh, 2013a;Harvey, Kneller, & Campbell, 2013a;Kneller & Harvey, 2016;Read, Yuille, & Tollestrup, 1992;Yuille & Tollestrup, 1990), three reveal an adverse effect of alcohol intoxication on identification accuracy (Bayless et al, 2018;Dysart et al, 2002;Read et al, 1992). Read et al (1992, Experiment 2) found an alcohol-linked reduction in face identification accuracy, but from a mock-perpetrator rather than mock-witness perspective.…”
mentioning
confidence: 99%